2011
DOI: 10.1111/j.1574-6968.2011.02255.x
|View full text |Cite
|
Sign up to set email alerts
|

Thioridazine affects transcription of genes involved in cell wall biosynthesis in methicillin-resistant Staphylococcus aureus

Abstract: The antipsychotic drug thioridazine is a candidate drug for an alternative treatment of infections caused by methicillin-resistant Staphylococcus aureus (MRSA) in combination with the β-lactam antibiotic oxacillin. The drug has been shown to have the capability to resensitize MRSA to oxacillin. We have previously shown that the expression of some resistance genes is abolished after treatment with thioridazine and oxacillin. To further understand the mechanism underlying the reversal of resistance, we tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 43 publications
0
26
0
2
Order By: Relevance
“…We do not believe that the phenothiazine actually has a direct effect on the genes, but rather limits or obviates access to calcium by calcium signalling-dependent systems. That this may indeed be true is supported by the wide-ranging effects that the phenothiazine has on hundreds of genes of mycobacteria [18,27] as well as the many genes of S. aureus [26] where calcium signalling plays a major role. Nevertheless, it remains for future studies to assess accurately the role played by the phenothiazines in mechanisms that lead to resistance.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We do not believe that the phenothiazine actually has a direct effect on the genes, but rather limits or obviates access to calcium by calcium signalling-dependent systems. That this may indeed be true is supported by the wide-ranging effects that the phenothiazine has on hundreds of genes of mycobacteria [18,27] as well as the many genes of S. aureus [26] where calcium signalling plays a major role. Nevertheless, it remains for future studies to assess accurately the role played by the phenothiazines in mechanisms that lead to resistance.…”
Section: Discussionmentioning
confidence: 74%
“…In recent years, phenothiazines have been shown to affect the expression of genes that code for components of the cell wall of Staphylococcus aureus [26] as well as essential genes, including efflux pump genes, of Mycobacterium tuberculosis [18,27]. These studies were conducted with concentrations of TZ that exceeded the MIC against the respective organism.…”
Section: Discussionmentioning
confidence: 99%
“…45 The antipsychotic phenothiazine thioridazine (Figure 3e) has been demonstrated to increase the susceptibility of MRSA to oxacillin 46 and dicloxacillin 47 in a number of clinical isolates. 47 It was shown that the oxacillin-induced transcription of mecA and expression of PBP2a 46a is reduced in the presence of thioridazine, as is transcription of several genes belonging to the VraSR regulon. 46b Thioridazine has also long been known to exhibit antibiotic effects against M. tuberculosis , 48 including multi-drug resistant strains, though not at clinically relevant concentrations.…”
Section: Screening Of Previously Approved Drugsmentioning
confidence: 99%
“…The short period of exposure to bifurans and MRSA in this animal model was selected to reduce interference from the host defense mechanisms. The used bifurans were able to resensitize MRSA to methicillin, ampicillin, and ciprofloxacin (Table 1), which may indicate the potential of such antistaphylocoocal compounds to abolish the expression of some resistance genes involved in cell-wall biosynthesis, reflecting the ability of these small molecules to overcome the cell-membrane barrier 21. In a previous study, a dicationic bifuran similar to 1B was reported to bind specific human telomeric quadruplex in more than one groove 22…”
Section: Discussionmentioning
confidence: 89%